Assessment of the Relationship between Green Brand Positioning, Consumer Attitudes, and Intent to Purchase Sustainable Products. - Anwar, Misbahul; Indratno, Diana Leli; Wibowo, Sutrisno; Aulyda, Widy (East Asian Journal of Multidisciplinary Research, 2024)
This study examines how Green Brand Positioning, Brand Attitude, and Brand Knowledge impact Green Purchase Intention. The independent variables include positioning, attitude, and green brand knowledge, while green purchase intention is the dependent variable, with green brand knowledge acting as a moderator. The research focuses on The Body Shop beauty brand and includes 236 participants. Data were analyzed using Structural Equation Modeling (SEM) with AMOS 21. The results show that green brand positioning positively and significantly influences green purchase intention, as do green brand attitude and knowledge. However, there is no significant difference in the effect of green brand positioning on purchase intention when considering different levels of green brand knowledge.